Probing strong dynamics with cosmic neutrinos - Anchordoqui, Luis Alfredo (2019)
IceCube has observed 80 astrophysical neutrino candidates in the energy range 0.02 ≲ Eν / PeV ≲ 2. Deep inelastic scattering of these neutrinos with nucleons on Antarctic ice sheet probe center-of-mass energies √ s ∼ 1     TeV. By comparing the rates for two classes of observable events, any departure from the benchmark (perturbative QCD) neutrino-nucleon cross section can be constrained. Using the projected sensitivity of South Pole next-generation neutrino telescope we show that this facility will provide a unique probe of strong interaction dynamics. In particular, we demonstrate that the high-energy high-statistics data sample to be recorded by IceCube-Gen2 in the very near future will deliver a direct measurement of the neutrino-nucleon cross section at √ s ∼ 1 TeV, with a precision comparable to perturbative QCD informed by HERA data. We also use IceCube data to extract the neutrino-nucleon cross section at √ s ∼ 1 TeV through a likelihood analysis, considering (for the first time) both the charged-current and neutral-current contributions as free parameters of the likelihood function.